DreadLock - (:unkn) unknown (My University, 2023)
Το μουσικοχορευτικό έργο με τίτλο DreadLock 1 ολοκληρώθηκε στην Αθήνα, τον Σεπτέμβριο του έτους 2022, στα πλαίσια της δεύτερης διπλωματικής εργασίας της συνθέτριας Αλεξάνδρας Τσουκαλά, προπτυχιακής φοιτήτριας του Τμήματος Μουσικών Σπουδών του Ιονίου Πανεπιστημίου και αποτελεί την τελευταία σύνθεση στα πλαίσια της ακαδημαϊκής της πορείας.

The music-dance work entitled DreadLock 1 was completed in Athens, in September of the year 2022, as part of the second diploma thesis of the composer Alexandra Tsoukalas, an undergraduate student of the Department of Music Studies of the Ionian University, and is the last composition in the context of her academic career.
DreadLock
Keywords: Χορός, Σύνθεση; Dance, Composition